PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum L.) - Ahmad Khafid Afianto; Djarwatiningsih Djarwatiningsih; Agus Sulistyono (Plumula : Berkala Ilmiah Agroteknologi, 2020)
Tomato (Lycopersicum esculentum L.) has a high market demand prospect. Low production of tomato plants can be caused by providing nutrients that are not optimal for plants. The growth and production of tomato plants can be optimized by providing various treatments, including the provision of appropriate and balanced nutrition using liquid organic fertilizer (POC) (NASA) and the right time interval for administration. This study aimed to determine the effect of NASA POC concentration and the time interval of administration on the growth and yield of tomato plants carried out at UPT 3 Agricultural Service, Kebomas District, Gresik Regency, East Java in December 2019 - March 2020. The study used a completely randomized design (CRD). two factors which are repeated three times. The first factor is the concentration of POC (NASA), consisting of four levels, namely without the provision of NASA POC (control) (P0), 1 ml / l water (P1), 2 ml / l water (P2), and 3 ml / l water (P3). The second factor is the interval of time of administration which consists of three levels, namely once a week (V1), once every 2 weeks (V2), and once every 3 weeks (V3). There was a very real interaction in the combination treatment of P3V2 on the height of tomato plants at the age of 40 days after planting (DAP) (68.06), 50 DAP (80.56), 60 DAP (86.06), and the number of leaves at 40 DAP (20.11. ), 50 DAP (26.56), 60 DAP (35.11).